1998
DOI: 10.1007/s003390051121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of methods for measuring. the apparent barrier height on an atomic scale

Abstract: Atomic-scale lateral variations in the apparent barrier height, which are a measure of the decay of the conductance with tip-sample distance in the scanning tunneling microscope, have been measured with three different methods. In general, a lateral variation of 10-25% is obtained within the unit cell of the reconstructed Au(110) surface. Furthermore, it is revealed that the absolute values, deduced from measurements of the tip-surface distance as a function of tunnel voltage, are approximately 30% lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…When the tip approaches the surface from a reference feedback position, the logarithm of tunneling current, log I (Δ z ), increases linearly following a one-dimensional tunneling model. This is a typical result for metal surfaces studied in previous research. When the tip reaches Δ z = −7 Å, the curves show a steep “current jump”, indicating a change from vacuum tunneling to conductive current. This can be explained by an electrical contact forming between the tip atoms and the surface atoms.…”
Section: Molecular Manipulationsupporting
confidence: 74%
See 2 more Smart Citations
“…When the tip approaches the surface from a reference feedback position, the logarithm of tunneling current, log I (Δ z ), increases linearly following a one-dimensional tunneling model. This is a typical result for metal surfaces studied in previous research. When the tip reaches Δ z = −7 Å, the curves show a steep “current jump”, indicating a change from vacuum tunneling to conductive current. This can be explained by an electrical contact forming between the tip atoms and the surface atoms.…”
Section: Molecular Manipulationsupporting
confidence: 74%
“…As the first step, the authors measured tip-displacement Δ z from the reference probe position z ref to the contact position against the surface. The contact position was defined as a “current jump”, indicating the change from vacuum electron tunneling to conductive current. In the actual measurement of I (Δ z ), the dynamic range of the current amplifier was limited when the tip was scanned along the z -direction over the full tip-displacement range. For this reason, the values of I (Δ z ) were measured as a partial data series obtained at different feedback positions with tunneling currents I of 7, 70, 700, and 7000 pA and a displacement Δ z of ±3 Å.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the tip−SAM surface contact, the ln( I )− Z relationship increases linearly as the tip approaches the surface. The tunneling barrier height, Φ, can be calculated using where I is the tunneling current and Z is the tip−surface separation. After contact, the tunneling current continues to increase linearly, with a larger slope, as the tip penetrates into the SAM. The first turning point (indicated in Figure A) defines the tip−methyl group contact position, at which I − V curves are acquired, as shown in Figure B.…”
Section: Mimicking Sam-based Devices Using Stm Measurementsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] On the other hand, surprisingly few reports on voltage-resolved a measurements are available. [16][17][18][19][20][21] For example, a on the reconstructed Au͑111͒ surface was reported to show a voltage polarity dependence, which was suggested to result from the surface dipole layer originating from the reconstruction. 19 In a subsequent study no voltage polarity dependence was found.…”
mentioning
confidence: 99%